On Perishing Poverty and Patriarchy: A Narrative Inquiry Exploring Women’s Agency in Rural Java - Herlina Dedy Listiani; Keppi Sukesi; Wike Wike (Jurnal Ilmu Sosial dan Humaniora, 2025)
This article aims to explore rural women's agency by focusing on lived experiences in perceiving and navigating the intersecting challenges of poverty and patriarchal structure in their everyday lives at the Kendalrejo Village-Pemalang Regency, Central Java. Ten low-income women were purposively sampled and invited to in-depth interviews and Focus Group Discussions (FGD), which allowed them to share detailed narratives of their lives. Using a narrative inquiry approach, the research portrays that despite the injustice and discrimination experienced by women in the domestic and public sphere, they managed to negotiate, actualize, and participate. This underscores another finding about the trajectory, shifting, and dynamics in rural settings regarding women’s experiences in the face of pervasive male dominance norms and the harsh realities of economic adversity. Toward a unique narrative of women, this study is crucial for providing meaningful policies and intervention recommendations to support women living in the rural realm.